Diagnostic Performance and Tolerability of Saliva and Nasopharyngeal Swab Specimens in the Detection of SARS-CoV-2 by RT-PCR - Ahti Jaakko; Österback Riikka; Keskitalo Anniina; Mokkala Kati; Vidbäck Siina; Veikkolainen Ville; Vuorinen Tytti; Peltola Ville; Hakanen Antti J; Waris Matti; Laine Miia (United States, 2025)
Saliva is a promising alternative for a nasopharyngeal swab (NPS) in specimen collection to detect SARS-CoV-2. We compared the diagnostic performance and tolerability of saliva collection versus NPS in a clinical setting. Paired NPS and saliva specimens were collected sequentially from participants (n = 250) at the Turku University Hospital drive-in coronavirus testing station in the spring of 2022, with Omicron BA.2 as the dominant SARS-CoV-2 variant. Discomfort and preference for the sampling method were assessed. The specimens were analyzed for SARS-CoV-2 using real-time multiplex reverse transcriptase PCR (RT-PCR) with a laboratory-developed test (LDT) and two commercial kits (PerkinElmer SARS-CoV-2 and PerkinElmer SARS-CoV-2 Plus) for several target genes. Among the 250 participants, 246 had respiratory symptoms. With LDT, SARS-CoV-2 was detected in 135 and 134 participants from NPS and saliva, respectively. Of the 250 specimens, 11 gave a discordant outcome, resulting in excellent agreement between the specimen types (Cohen's kappa coefficient of 0.911; P = 0.763). The cycle threshold (CT) values of LDT and commercial kit target genes were significantly lower from NPS than from saliva. A total of 172 (69%) participants assessed saliva sampling as more tolerable than NPS (P < 0.0001). Our findings present saliva as an applicable alternative for SARS-CoV-2 diagnostics. However, the lower CT values obtained from NPS indicate that NPS may be a slightly more sensitive specimen type. Participants preferred saliva sampling, although delivering an adequate volume of saliva was challenging for some participants.
IMPORTANCE The extensive testing of SARS-CoV-2 is vital in controlling the spread of COVID-19. The reference standard for specimen collection is a nasopharyngeal swab (NPS). However, the discomfort of NPS sampling, the risk of nosocomial infections, and global material shortages have accelerated the development of alternative testing methods. Our study demonstrates that patients tolerate saliva sampling better than NPS. Of importance, although the RT-PCR qualitative test results seem to correspond between NPS and saliva, we show significantly lower CT values for NPS, compared to saliva, thus contradicting the suggested superiority of the saliva specimen over NPS in the detection of the Omicron variants of SARS-CoV-2. Future research is still required to enable individual planning for specimen collection and to determine the effects of different SARS-CoV-2 variants on the sensitivity of the saliva matrix.